Exploration of the Wound Healing Activity of Ethanol Extract-Based Ointment from Curry Leaves on the Wound Healing Process - Andilala, Andilala; Sihombing, Juliana Sion (Journal of Food and Pharmaceutical Sciences, 2025)
Indonesian society widely utilizes traditional medicinal plants, including curry leaves (Murraya koenigii L.), which contain alkaloids, tannins, flavonoids, saponins, steroids, and triterpenoids known to possess antioxidant and anti-inflammatory properties. This study aims to formulate curry leaf ethanol extract ointments as wound healing agents and to determine the most effective concentration in accelerating incision wound recovery. Five treatments were prepared: ointment base (negative control), Betadine 10% (positive control), and curry leaf ethanol extract ointments at concentrations of 5%, 10%, and 15%. The ointments were assessed for physical properties and tested on male white rats. The results showed that all formulations met the organoleptic, stability, homogeneity, pH, adhesion, and spreadability requirements. Quantitative wound-healing analysis demonstrated that the 15% extract ointment produced the highest healing percentage, achieving 56.4% on day 5, 70.9% on day 8, and 100% by day 14, outperforming Betadine 10% (80% by day 14). One-way ANOVA revealed significant differences among treatment groups (p < 0.05), with the 15% formulation showing the most effective therapeutic response. These findings indicate that curry leaf ethanol extract ointment, particularly at a 15% concentration, has strong potential as a topical Wound Healing agent.